Immune Plasma for the Treatment of COVID-19: Lessons Learned so far - Schrezenmeier, Hubert; Hoffmann, Simone; Hofmann, Henrike; Appl, Thomas; Jahrsdörfer, Bernd; Seifried, Erhard; Körper, Sixten (Hämostaseologie, 2023)
COVID-19 convalescent plasma (CCP) has been explored as one of the treatment options for COVID-19. Results of many cohort studies and clinical trials have been recently published. At first glance, the results of the CCP studies appear to be inconsistent. However, it became clear that CCP is not beneficial if CCP with low anti-SARS-CoV-2 antibody concentrations is used, if it is administered late in advanced disease stages, and to patients who already mounted an antibody response against SARS-CoV-2 at the time of CCP transfusion. On the other hand, CCP may prevent progression to severe COVID-19 when very high-titer CCP is given early in vulnerable patients. Immune escape of new variants is a challenge for passive immunotherapy. While new variants of concern developed resistance to most clinically used monoclonal antibodies very rapidly, immune plasma from individuals immunized by both a natural SARS-CoV-2 infection and SARS-CoV-2 vaccination retained neutralizing activity against variants. This review briefly summarizes the evidence on CCP treatment to date and identifies further research needs. Ongoing research on passive immunotherapy is not only relevant for improving care for vulnerable patients in the ongoing SARS-CoV-2 pandemic, but even more as a model for passive immunotherapy in case of future pandemics with a newly evolving pathogen. Compared to other drugs, which must be newly developed in a pandemic (e.g., monoclonal antibodies, antiviral drugs), convalescent plasma is rapidly available, inexpensive to produce, and can be adaptive to viral evolution by selection of contemporary convalescent donors.
Keywords: immune plasma; convalescent plasma; COVID-19; vaccination